HIV-1 Langerhans' cell tropism associated with heterosexual transmission of HIV - Luis E. Soto-Ramirez (2018)
Heterosexual transmission by vaginal intercourse accounts for most transmission of human immunodeficiency virus-type 1 (HIV-1) in Africa and Asia but is less important in the HIV-1 epidemics of the United States and Western Europe. Epithelial Langerhans' cells (LCs) represent a possible source of initial cell contact for vaginal infection. Fifteen primary isolates of HIV-1 from U.S. homosexuals and 18 HIV-1 isolates from Thailand heterosexuals were evaluated for growth in LCs of U.S. origin. All the viruses from the Thai heterosexuals, which were subtype E, grew more efficiently in the LCs than any of the viruses from the U.S. homosexuals, which are subtype B. These results suggest that LC tropism is associated with the efficiency of heterosexual transmission of HIV.